AFRICAN-AMERICAN THEATER & THE DECONSTRUCTION OF THE AMERICAN DREAM - Valente, Marcela Iochem (A Cor das Letras, 2017)
Lorraine Hansberry was an African-American playwright who used her plays as a way of protest against the injustice towards the African descendants in the USA and fought against the prejudice and discrimination faced by her people at that time. Her work was a site for many discussions that were very relevant to further movements such as the civil rights one. She showed in her work that although the USA was supposed to be the Land of Opportunity, the prosperity of this land as well as the ideals from the American Dream were not available the same way to all citizens, just to those who could fit the mainstream American stereotype. This article is going to show that Theater can be an important way of self-representation, a site for relevant discussions, and a way of subverting patriarchal discourses.